Neuroplasticity and rehabilitation - Raskin, Sarah A. (New York : Guilford Press, 2011)
"Brain plasticity is the focus of a growing body of research with significant implications for neurorehabilitation. This state-of-the-art volume explores ways in which brain-injured individuals may be helped not only to compensate for their loss of cognitive abilities, but also possibly to restore those abilities. Expert contributors examine the extent to which damaged cortical regions can actually recover and resume previous functions, as well as how intact regions are recruited to take on tasks once mediated by the damaged region. Evidence-based rehabilitation approaches are reviewed for a range of impairments and clinical populations, including both children and adults"--Provided by publisher.
Chapter 1. Introduction: current approaches to rehabilitation / Sarah A. Raskin -- Part I. Reorganization in the central nervous system: Chapter 2. Neuronal organization and change after brain injury / Bryan Kolb, Jan Cioe, and Preston Williams; Chapter 3. Experience-dependent changes in nonhumans / Theresa A. Jones; Chapter 4. Motor and sensory reorganization in primates / Randolph J. Nudo and Scott Bury; Chapter 5. Cognitive reserve / Yaakov Stern; Chapter 6. Practice-related changes in brain activity / Sarah A. Raskin, Ginger N. Mills, and Julianne T. Garbarino -- Part II. Interventions for motor and cognitive deficits: Chapter 7. Activity-based interventions for neurorehabilitation / David M. Morris and C. Scott Bickel; Chapter 8. Malleability and plasticity in the neural systems for reading and dyslexia / Bennett A. Shaywitz and Sally E. Shaywitz; Chapter 9. Neuroplasticity and rehabilitation of attention in children / Jennifer A. Engle and Kimberly A. Kerns; Chapter 10. Language therapy / Susan A. Leon, Lynn M. Maher, and Leslie J. Gonzalez Rothi; Chapter 11. Plasticity of high-order cognition: a review of experience-induced remediation studies for executive deficits / Redmond G. O'Connell and Ian H. Robertson; Chapter 12. Neuroplasticity and the treatment of executive deficits: conceptual considerations / Rema A. Lillie and Catherine A. Mateer; Chapter 13. What rehabilitation clinicians can do to facilitate experience-dependent learning / McKay Moore Sohlberg and Laurie Ehlhardt Powell; Chapter 14. Pharmacological therapies, rehabilitation, and neuroplasticity / John C. Freeland.
Includes bibliographical references and index.
Keywords: Neuroplasticity; Brain -- Wounds and injuries -- Patients -- Rehabilitation; Neuronal Plasticity -- physiology; Brain Injuries -- rehabilitation; Cognitive Reserve -- physiology; klinička neuropsihologija